2015
DOI: 10.1007/s00701-015-2599-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the subthalamic nucleus: histological verification and 9.4-T MRI correlation

Abstract: This study supports the anatomical accuracy of the MRI-guided and MRI-verified method of STN DBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…7 Although evidence supports this method of STN-DBS in improving the motor symptoms of those with PD, it is noted that on rare occasions (owing to anatomical variations in brain structure), the use of the central tract may lead to detrimental effects, thus necessitating its omission when performing this procedure. 8,9 In this present study sample, it was found that the central tract is only used as the final lead placement in 63.83% of reported cases, which is significantly less than previously reported literature. This therefore emphasises the importance of accurate preoperative and intraoperative planning and microelectrode testing, in conjunction with awake macro-stimulation, to assess real-time clinical response.…”
Section: Discussioncontrasting
confidence: 56%
“…7 Although evidence supports this method of STN-DBS in improving the motor symptoms of those with PD, it is noted that on rare occasions (owing to anatomical variations in brain structure), the use of the central tract may lead to detrimental effects, thus necessitating its omission when performing this procedure. 8,9 In this present study sample, it was found that the central tract is only used as the final lead placement in 63.83% of reported cases, which is significantly less than previously reported literature. This therefore emphasises the importance of accurate preoperative and intraoperative planning and microelectrode testing, in conjunction with awake macro-stimulation, to assess real-time clinical response.…”
Section: Discussioncontrasting
confidence: 56%
“…Sections of 20 µm were obtained using a sliding microtome (Histoslide 2000R, Leica, Nussloch, Germany) similar to the study of Al‐Helli and coworkers [Al‐Helli et al, ]. The specimens were cut axially.…”
Section: Methodsmentioning
confidence: 99%
“…These blocks were treated in the same manner as the midbrain specimens. Volumes were determined before dehydrating the specimens in ethanol as well as after incubation in paraffin wax, measuring Sections of 20 mm were obtained using a sliding microtome (Histoslide 2000R, Leica, Nussloch, Germany) similar to the study of Al-Helli and coworkers [Al-Helli et al, 2015]. The specimens were cut axially.…”
Section: Histologymentioning
confidence: 99%
“…Although our reconstruction is principled and preliminary results show correspondence with the clinical standard-of-care, there is no “gold standard” (other than postmortem histology) for verifying these results [1416]. In addition, our intrapatient linear registration methods did not take pneumocephalus-related intraoperative brain shift into account.…”
Section: Discussionmentioning
confidence: 98%